YOLO-VOLO-LS: A Novel Method for Variety Identification of Early Lettuce Seedlings - Zhang, Pan; Li, Daoliang (Frontiers in Plant Science, 2022)
Accurate identification of crop varieties is an important content of smart agriculture, which is not only essential for the management of later crop differences, but also has a significant effect on unmanned operations in planting scenarios such as facility greenhouses. In this study, five kinds of lettuce under the cultivation conditions of greenhouse were used as the research object, and a classification model of lettuce varieties with multiple growth stages was established. First of all, we use the-state-of-the-art method VOLO-D1 to establish a variety classification model for the 7 growth stages of the entire growth process. The results found that the performance of the lettuce variety classification model in the SP stage needs to be improved, and the classification effect of the model at other stages is close to 100 %; Secondly, based on the challenges of the SP stage dataset, we combined with the advantages of the target detection mechanism and the target classification mechanism, innovatively proposed a new method of variety identification for the SP stage, called YOLO-VOLO-LS. Finally, we use this method to model and analyze the classification of lettuce varieties in the SP stage. The result shows that the method can achieve excellent results of 95.961, 93.452, 96.059, 96.014, 96.039 in Val-acc, Test-acc, Recall, Precision, F1-score, etc., respectively. Therefore, the method proposed in this study has a certain reference value for the accurate identification of varieties in the early growth stage of crops.